Riding the Escalator: How Dangerous is it Really? - Louisa H. Schminke; Victor Jeger; Dimitrios S. Evangelopoulos; Heinz Zimmerman; Aristomenis K. Exadaktylos (Western Journal of Emergency Medicine, 2013)
Introduction: About 10,000 escalator-related injuries per year result in emergency departmenttreatment in the United States. Since the 1990s, a steady increase has been reported, but fewstatistics on escalator-related injuries have been published worldwide. We have therefore analyzedescalator accident statistics in admissions to our hospital in Switzerland since 2000.Methods: Using retrospective electronic patient chart analysis, we included in our study patients>16 years treated over an 11-year period. We categorized patients in terms of gender, age andassociated risk factors, and classified accidents according to day, time, location and cause. Resultingtrauma was categorized according to type and location. We divided post-admission treatment intosurgical and conservative, and into treatment as an outpatient, in a short-stay unit, or as a hospitaladmission. Women and men were compared using Fisher’s exact test.Results: We identified 173 patients with 285 discrete injuries. Of these, 87 patients (50%) werewomen. Fifty-three (61%) of the women and 38 (44%) of the men were >60 years old (P = 0.033).Fifty percent of the men (43/86)of the men, but only 7% (6/87) of the women showed signs of alcoholintoxication (P < 0.0001). Accidents in women occurred predominantly on Tuesdays (19/87; 22%)between 12PM and 6PM (35/87; 40%), and in men on Saturdays (16/86; 19%) between 6PM and12AM (29/86; 34%; P = 0.0097). Sixty-two percent (44/71) of the accidents were in public transportfacilities and 30% (21/71) in shopping centers. The majority of injuries in women were to the lowerextremities (49/87; 56%), while most accidents in men were to the head and neck (51/86; 59%; P =0.0052). About half (90; 52%) of the patients were treated conservatively. Almost half of all patients(76, 44%) required hospital admission. Of those, 45% left the hospital within 24 hours of admission(short stay unit) and 55% stayed longer than 24 hours.Conclusion: Escalator accidents can result in severe trauma. Significant gender differences inescalator accidents have been observed. Alcohol intoxication and age are significant risk factors inescalator-related accidents and might be possible targets for preventive measures.